Methods of Introduction of Primary Dental Prevention in Preschool Children - Turavi Dilnozai Jurabek; Rahimberdiyev Rustam (Genius Journals, 2023)
The major oral diseases (dental caries and inflammatory periodontal disease) are considered manageable and often preventable. However, these diseases are among the most common in children in our country [2, 3, 6]. It is also known that children's health is highly dependent on parental involvement in the teaching of reasonable hygiene skills. Thus, the study of parents' preventive knowledge and oral hygiene habits is a relevant issue. Since public attitudes may change over time, it is reasonable to assume that both the level of hygiene culture and the degree of parental responsibility with regard to the prevention and treatment of major dental diseases in children will change [4]. Current organizational approaches and treatments cannot curb the increasing prevalence and intensity of oral diseases. Therefore, dentists need to assist in this task by primary prevention of dental diseases, the implementation of which will reduce the likelihood of the occurrence of these diseases, reduce the need for their treatment, and allow dentists to devote more time to disease prevention. Parents can play a major role in introducing primary prevention of dental disease to their children.
Keywords: dental; reduce; prevention; major